2022
DOI: 10.1186/s12957-022-02801-0
|View full text |Cite
|
Sign up to set email alerts
|

AXL, along with PROS1, is overexpressed in papillary thyroid carcinoma and regulates its biological behaviour

Abstract: Background AXL, a TAM tyrosine kinase receptor, plays an essential role in the pathogenesis of various solid tumours. This study explores the role of AXL and its ligand PROS1 in the generation and biological behaviour of papillary thyroid cancer (PTC). Methods The expression levels of AXL in PTC cancer tissue were analysed using immunohistochemistry (IHC) staining. The expression levels of AXL in PTC and normal thyroid cell lines were analysed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that Gas6 binds to all three TAM receptors, while PROS1 activates Tyro3 (with high affinity) and Mer, but not AXL [34]. However, recent studies have provided evidence that PROS1 can also activate AXL in tumor cells, thereby promoting tumor cell proliferation and invasiveness [21,35,36]. PROS1 and TAM receptors signaling pathways have been recognized as a crucial negative regulator of the immune system, playing a role in limiting the intensity and duration of immune responses [17,37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that Gas6 binds to all three TAM receptors, while PROS1 activates Tyro3 (with high affinity) and Mer, but not AXL [34]. However, recent studies have provided evidence that PROS1 can also activate AXL in tumor cells, thereby promoting tumor cell proliferation and invasiveness [21,35,36]. PROS1 and TAM receptors signaling pathways have been recognized as a crucial negative regulator of the immune system, playing a role in limiting the intensity and duration of immune responses [17,37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study reveals that Pros1-Axl plays a signi cant communication role among different cells. Previous research has suggested that Pros1-Axl is involved in regulating thyroid papillary carcinoma cell proliferation and migration, as well as modulating immune-in ammatory responses in brain injury [35,36] . However, there is currently limited research investigating the role of Pros1-Axl in oxidative stress reactions and SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Zhu et al demonstrated that ITGA5 overexpression promotes poor prognosis in GAC [ 65 ]. In the PROS pathway, the PROS1 ligand and its receptor AXL are overexpressed in thyroid cancer, while AXL blockade suppresses the invasion of thyroid cancer cells [ 66 ]. Within the TME, the tumor homing of mesenchymal stromal cells is regulated by the MIF-(CD74 + CXCR4) ligand–receptor pair in the MIF pathway [ 67 ].…”
Section: Discussionmentioning
confidence: 99%